Does Eagerness for Physical Activity Matter? The Association Between Eagerness and Physical Activity Among Adolescents - Mikalsen, Hilde Kristin; Lagestad, Pål; Bentzen, Marte; Säfvenbom, Reidar (Frontiers in Public Health, 2019)
This study investigated the association between perceived parental support and eagerness for physical activity (EPA) among adolescents, and the association between EPA and physical activity. We further examined whether perceived athletic competence (PAC) mediates a presumed association between EPA and physical activity level, when controlling for gender. This study included 320 adolescents (aged 12–13) from 18 schools in two medium-sized Norwegian municipalities. Questionnaires and accelerometers were assessed during spring 2017. Structural equation modeling was applied to examine the associations. Standard regression coefficients are presented. Data demonstrated that perceived parental support was positively associated with EPA (β = 0.52), and eagerness was positively associated with PAC (β = 0.52). Both EPA (β = 0.20) and PAC (β = 0.24) were also positively associated with moderate to vigorous physical activity (MVPA). When mediating the relationship between EPA and MVPA, through PAC, the effect on MVPA increased (from β = 0.20 to β = 0.32). Analysis revealed that 87% of the adolescents fulfilled the national health recommendations for physical activity. This study highlights the relevance of EPA and PAC in studies of physical activity among adolescents, and the impact of perceived parental support for adolescents' EPA and physical activity level.